2002
DOI: 10.1002/1522-2683(200207)23:14<2223::aid-elps2223>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic evaluation of cell preparation methods in primary hepatocyte cell culture

Abstract: In vitro liver preparations are being used increasingly to study various aspects of chemical hepatotoxicity and thus have become powerful alternatives to in vivo toxicologic models. Primary hepatocyte culture systems are especially useful in screening cytotoxic and genotoxic compounds and assessing biochemical lesions associated with chemical exposure. We have begun to use this approach in combination with proteomic analysis to construct a molecular "toxicoproteomic" test system for a broad range of relevant a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Comparative proteomic analysis requires a high degree of spatial and quantitative reproducibility. Although protein purification, resolubilization, separation and identification techniques are well-documented, only a few publications report the importance of cell or biological sample preparation before proteomic analysis [22][23][24][25]. Furthermore, as already demonstrated with our model [26], BBCEC are able to differentiate in a manner close to the in vivo situation under the influence of glial secretions only if they are cultured on a collagen matrix and in the presence of serum.…”
Section: Introductionmentioning
confidence: 67%
“…Comparative proteomic analysis requires a high degree of spatial and quantitative reproducibility. Although protein purification, resolubilization, separation and identification techniques are well-documented, only a few publications report the importance of cell or biological sample preparation before proteomic analysis [22][23][24][25]. Furthermore, as already demonstrated with our model [26], BBCEC are able to differentiate in a manner close to the in vivo situation under the influence of glial secretions only if they are cultured on a collagen matrix and in the presence of serum.…”
Section: Introductionmentioning
confidence: 67%
“…Witzmann et al [11], using primary hepatocyte cell culture, showed that the recovery of the cells from monolayer cell culture by scraping, washing and centrifugal pelleting of the cells, followed by solubilization, results in the introduction of significant variability between the samples. Proteins localized in cytosolic, cytoskeletal or external compartments lost over half of their abundance during this procedure.…”
Section: Cell Culturesmentioning
confidence: 99%
“…Indeed, a proteomic approach has been successfully used to assess the effects of physical manipulation and cell harvesting techniques on distribution and/or loss of proteins in rat hepatocytes [7]. In our laboratory, both short-term hepatocyte cultures on collagen [8,9] and long-term (weeks to months) cultures of adult hepatocytes (unpublished) and hepatic stem cells [10] are routinely employed and protein expression profiles during these culture periods are critical to interpret hormonal effects on differentiated cell function.…”
Section: Introductionmentioning
confidence: 99%